Handbook of Maintenance Planning and Scheduling - Nyman, Don; Levitt, Joel (Industrial Press, 2001)
Annotation Well-planned, properly scheduled, and effectively communicated jobs accomplish more work, more efficiently, and at a lower cost. This work will disturb operations less frequently, and be accomplished with higher quality, greater job satisfaction, and higher organizational morale than jobs performed without proper preparation. Maintenance Planning, Scheduling and Coordination focuses on and deals specifically with the preparatory tasks that lead to effective utilization and application of maintenance resources. It is a vital training document for planners, an educational document for those to whom planners are responsible, and a valuable guide for those who interface with the planning and scheduling function and are dependent upon the many contributions of planning and scheduling operational excellence.
Keywords: elektronické knihy; electronic books